The Lexicographic Presentation of Social Media Marketing Terms In English and Uzbek Language Dictionaries - Mirova Nargiza Sayfullayevna (Indonesian Journal Publisher, 2026)
In the context of rapid digitalization and the global expansion of social media platforms, Social Media Marketing (SMM) has developed a dynamic and specialized terminology predominantly rooted in English. This article provides a comparative lexicographic analysis of SMM terms as they appear in English-language glossaries and dictionaries versus their representation (or absence) in Uzbek lexicographic sources. Drawing on specialized online English glossaries and recent Uzbek academic research, the study reveals significant differences in standardization, borrowing patterns, translation strategies, and terminological adaptation. While English lexicography offers mature, comprehensive, and readily accessible resources, Uzbek sources remain underdeveloped, relying heavily on transliteration, partial translation, and ad hoc academic compilations. The findings emphasize the urgent need for a standardized Uzbek terminological dictionary to support national linguistic policy, marketing education, and professional practice in the Republic of Uzbekistan